Two new genera and four new species of Mydidae (Diptera) from Madagascar - Kondratieff, B. C.; Carr, Ryan J.; Irwin, Michael E. (Zootaxa, 2005)
Two new genera and four new species of Mydidae are described from Madagascar. Hessemydas new genus, is proposed to include Leptomydas seyrigi Séguy, n. comb., H. tulear, n. sp., H. parkeri, n. sp.; and Mahafalymydas n. gen., is proposed for M. wiegmanni n. sp. and M. tuckeri n. sp.